Adsorpsi Kromium Heksavalen Menggunakan Nanokomposit ZnO/Kitosan dari Limbah Baterai Zn-C dan Kulit Udang - Garminingsih; Sunardi (Jurnal Ilmiah Teknik Kimia, 2025)
Zn-C batteries contain zinc, carbon, manganese dioxide, and ammonium chloride, which are difficult to decompose and pose risks to human health and the environment. Recycling Zn-C battery waste into zinc oxide (ZnO) offers a sustainable solution. When combined with chitosan, ZnO forms a composite material. This study analyzes the characteristics of ZnO/chitosan nanocomposites and determines optimal conditions for hexavalent chromium adsorption. The nanocomposite was synthesized by mixing ZnO from battery waste with chitosan from shrimp shells. FTIR analysis of chitosan showed characteristic peaks at 3.498 cm⁻¹, 2.875 cm⁻¹, 1.373 cm⁻¹, 1.613 cm⁻¹, 1.302 cm⁻¹, 1.554 cm⁻¹, 1.153 cm⁻¹, and 1.067 cm⁻¹, while ZnO had a peak at 502 cm⁻¹. XRD analysis identified 2θ peaks at 9.22º, 19.13º, 23.04º, 26.23º, 31.62º, 34.39º, 36.17º, and 56.54º. Optimal adsorption occurred with 20 mg nanocomposite, 60 minutes contact time, and 5 ppm chromium concentration, achieving 94.61% efficiency.